Quellenin, a new anti-Saprolegnia compound isolated from the deep-sea fungus, Aspergillus sp. YK-76. (August 2018) - Takahashi, Konami; Sakai, Kazunari; Fukasawa, Wataru; Nagano, Yuriko; Sakaguchi, Sakiko; Lima, Andre; Pellizari, Vivian; Iwatsuki, Masato; Takishita, Kiyotaka; Yoshida, Takao; Nonaka, Kenichi; Fujikura, Katsunori; et al.
Abstract Saprolegnia parasitica, belonging to oomycetes, is one of virulent pathogen of fishes such as salmon and trout, and causes tremendous damage and losses in commercial aquacultures by saprolegniasis. Previously, malachite green, an effective medicine, had been used to control saprolegniasis. However, this drug has been banned around the world due to its mutagenicity. Therefore, novel anti-saprolegniasis compounds are urgently needed. As a new frontier to discover bioactive compounds, we focused on the deep-sea fungi for the isolation of anti-saprolegniasis compounds. In this paper, on the course of anti-saprolegniasis agents from 546 cultured broths of 91 deep-sea fungal strains, we report a new compound, named quellenin (1) together with three known compounds, diorcinol (2), violaceol-I (3) and violaceol-II (4), from deep-sea fungusAspergillus sp. YK-76. This strain was isolated from anOsedax sp. annelid, commonly called bone-eating worm, collected at the São Paulo Ridge in off Brazil. Compounds 2, 3 and 4 showed anti-S. parasitica activity. Our results suggest that diorcinol and violaceol analogs and could be good lead candidates for the development of novel agents to prevent saprolegniasis.